Constitutional Limitations on the Power of the Missouri Legislature to Provide for Venue in Criminal Cases - Frank William Miller (Washington University Law Quarterly, 1958)
The purpose of this study is to define the right to trial in the county where the crime was committed, and, more significantly, to determine the precise extent to which the constitutional provisions which grant that right operate as a limitation on the legislative power to provide for venue in certain kinds of cases which present unusual practical difficulties. It is analytically convenient—and, I believe, factually accurate—to establish three mutually exclusive categories of venue cases: (1) Those in which there is no doubt where every part of the total course of criminal conduct occurred, and where every part occurred in a single county. (2) Those in which there is doubt-perhaps not resolvable under ordinary burden of proof rules-where some significant part of the total course of criminal conduct occurred. (3) Those in which there is no doubt where every part of the total course of criminal conduct occurred, but where-at least according to some rational view of the matter-some significant part occurred in one county and another significant part occurred in another county. To anticipate the conclusion reached in this Article, it appears that the constitutional mandate seriously limits the scope of legislative power in classes 1 and 2, but not in class 3. To discuss classes 1 and 2 together will contribute to clarity and understanding, so that will be done first.
Keywords: Constitutional law – Missouri; Venue